Measuring countries relative efficiencies in using development assistance: a data envelopment analysis approach - Mohamed F. Sakr; Kamal Samy Selim; Sherin Gamaleldin Taha (Future Business Journal)
Abstract Despite the presence of a considerable corpus of literature investigating the impact of aid on nations' development, the efficiency of utilizing this finite pool of development finance remains ambiguous. The main aim of this study is to address the existing research gap by examining the efficiency of utilizing such development assistance in achieving three specific Sustainable Development Goals (SDGs) from 2002 to 2020 using a Data Envelopment Analysis (DEA) methodology. Moreover, this study examines the theoretical underpinnings that show a correlation between the impact of aid on development and the governance and political structure of countries. The findings indicate that the efficiency of development assistance often falls short of optimal, underscoring the necessity for more attention to its administration, particularly in low-income countries. The efficiency of development assistance can be significantly enhanced by organizational improvements, resulting in a significant increase beyond 80%. The confirmation of the robustness of the findings was attained by the application of the bootstrapping methodology. Hence, it is crucial to recognize that while augmenting the levels of development assistance may hold significance, it alone may not be adequate to guarantee efficient utilization in bridging the financial gap required to meet the desired objectives of the SDGs by 2030.